2021
DOI: 10.1515/math-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Fractional calculus, zeta functions and Shannon entropy

Abstract: This paper deals with the fractional calculus of zeta functions. In particular, the study is focused on the Hurwitz ζ \zeta function. All the results are based on the complex generalization of the Grünwald-Letnikov fractional derivative. We state and prove the functional equation together with an integral representation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…For some applications, we refer to other studies, [4][5][6][7][8][9][10][11][12][13] and the references therein. For applied science, we refer to other studies [14][15][16][17][18][19] as an application in the theory of special functions.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…For some applications, we refer to other studies, [4][5][6][7][8][9][10][11][12][13] and the references therein. For applied science, we refer to other studies [14][15][16][17][18][19] as an application in the theory of special functions.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In fact, having an overview of the on-going contributions to the theory and applications of fractional calculus, which are continually appearing in some of the leading journals devoted to mathematical and physical sciences, biological sciences, statistical sciences, engineering sciences, and so on, the subject-matter, which we have dealt with in this review article, is remarkably important and potentially useful. Moreover, the interested future researchers will surely benefit from the listing of references to some of the other applications of various fractional-calculus operators in the mathematical and other sciences, which we have not considered in the preceding sections (see, for example, [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111]).…”
Section: Concluding Remarks and Observationsmentioning
confidence: 99%
“…Namely, it was shown that many real-world phenomena can be better modeled using fractional operators; see, e.g., previous studies. [14][15][16][17][18][19][20] This fact motivated many researchers to study fractional analogues of known functional inequalities; see, e.g., previous studies [21][22][23][24][25][26][27][28][29][30] and the references therein. In particular, in Anastassiou, 25 some fractional Sobolev-and Hilbert-Pachpatte-type inequalities were obtained with respect to ψ-fractional derivatives (see previous studies 16,31 ).…”
Section: Introductionmentioning
confidence: 99%